Freshwater adaptation in prickly sculpin (Pisces: Cottidae): intraspecific comparisons reveal evidence for water pH and Na+ concentration driving diversity in gill H+-ATPase and ion regulation - Liu, Shuang; Wilson, Jonathan M; Taylor, Eric B; Richards, Jeffrey G (Journal of experimental biology, 2022)
Phenotypic divergence is a hallmark of adaptive radiation. One example involves differentiation in physiological traits involved in ion regulation among species with contrasting lifestyles and living in distinct environments. Differentiation in ion regulation and its ecological implications among populations within species are, however, less well understood. To address this knowledge gap, we collected prickly sculpin (Cottus asper) from distinct habitat types including coastal rivers connected to estuaries, coastal lakes and interior lakes, all from British Columbia, Canada. We tested for differences in plasma Na+ and Cl-, gill Na+/K+-ATPase and H+-ATPase activity and protein abundance as well as changes in body mass and arterial blood pH in fish sampled from the field and acclimated to two different freshwater conditions in the laboratory: artificial lake water (ALW) and ion-poor water (IPW). We also tested for links between environmental water chemistry and the physiological characteristics associated with ion regulation. Transfer to IPW resulted in upregulation of gill Na+/K+-ATPase and H+-ATPase activity as well as increases in gill H+-ATPase protein expression level in each habitat compared with that in the common ALW treatment. Despite the presence of population-within-habitat-type differences, significant habitat-type effects were revealed in most of the ion regulation characteristics examined under different acclimation conditions. Significantly lower plasma Cl- was detected in fish from coastal rivers than in fish from the other two habitat types during the IPW treatment, which was also significantly lower compared with that in ALW. Similarly, gill Na+/K+-ATPase activity was lower in the coastal river populations in IPW than in fish from coastal and interior lakes, which was not in accordance with the protein expression in the gill. For gill H+-ATPase, fish from interior lake populations had the highest level of activity across all habitat types under all conditions, which was related to the protein levels in the gill. The activity of gill H+-ATPase was positively correlated with the combined effect of water Na+ and pH under the ALW treatment. Our results suggest that variation in habitat may be an important factor driving differences in gill Na+/K+-ATPase and H+-ATPase activity across populations of C. asper. Further, the combined effect of water Na+ and pH may have played a key role in physiological adaptation in C. asper during post-glacial freshwater colonization and dispersal.Phenotypic divergence is a hallmark of adaptive radiation. One example involves differentiation in physiological traits involved in ion regulation among species with contrasting lifestyles and living in distinct environments. Differentiation in ion regulation and its ecological implications among populations within species are, however, less well understood. To address this knowledge gap, we collected prickly sculpin (Cottus asper) from distinct habitat types including coastal rivers connected to estuaries, coastal lakes and interior lakes, all from British Columbia, Canada. We tested for differences in plasma Na+ and Cl-, gill Na+/K+-ATPase and H+-ATPase activity and protein abundance as well as changes in body mass and arterial blood pH in fish sampled from the field and acclimated to two different freshwater conditions in the laboratory: artificial lake water (ALW) and ion-poor water (IPW). We also tested for links between environmental water chemistry and the physiological characteristics associated with ion regulation. Transfer to IPW resulted in upregulation of gill Na+/K+-ATPase and H+-ATPase activity as well as increases in gill H+-ATPase protein expression level in each habitat compared with that in the common ALW treatment. Despite the presence of population-within-habitat-type differences, significant habitat-type effects were revealed in most of the ion regulation characteristics examined under different acclimation conditions. Significantly lower plasma Cl- was detected in fish from coastal rivers than in fish from the other two habitat types during the IPW treatment, which was also significantly lower compared with that in ALW. Similarly, gill Na+/K+-ATPase activity was lower in the coastal river populations in IPW than in fish from coastal and interior lakes, which was not in accordance with the protein expression in the gill. For gill H+-ATPase, fish from interior lake populations had the highest level of activity across all habitat types under all conditions, which was related to the protein levels in the gill. The activity of gill H+-ATPase was positively correlated with the combined effect of water Na+ and pH under the ALW treatment. Our results suggest that variation in habitat may be an important factor driving differences in gill Na+/K+-ATPase and H+-ATPase activity across populations of C. asper. Further, the combined effect of water Na+ and pH may have played a key role in physiological adaptation in C. asper during post-glacial freshwater colonization and dispersal.